Transformasi Manajemen Bisnis Syariah di Era Digital: Implikasi bagi Industri Halal - Desy Arum Sunarta; Amalia S Tapparang; Dian Novianti (Fakultas Ekonomi dan Bisnis Islam, 2026)
This study examines the transformation of Islamic business management in the digital era and its implications for the development of the halal industry. The rapid advancement of digital technologies has reshaped managerial practices across sectors, including Islamic business, where technological innovation must be aligned with Islamic values and principles. The primary objective of this study is to analyze patterns of digital transformation in Islamic business management and to explore how such transformation supports sustainability and competitiveness within the halal industry. This research adopts a literature review approach by synthesizing peer-reviewed academic publications indexed in reputable databases. The review integrates systematic literature review as the main method, supported by scoping review and bibliometric perspectives to map research trends, dominant themes, and conceptual developments in Islamic business management and digital transformation. The findings reveal that digital transformation in Islamic business management is characterized by the integration of technologies such as artificial intelligence, blockchain, and digital platforms to enhance operational efficiency, transparency, and accountability while maintaining compliance with Islamic principles. Digitalization also drives innovation in business models, strengthens organizational resilience, and facilitates inclusive financial services within the halal industry. Furthermore, the integration of Islamic values, including justice, compliance, and social benefit, positions digital business practices as instruments for achieving the objectives of maqashid shariah and long-term sustainability. This study concludes that digital transformation provides a strategic opportunity to advance Islamic business management beyond normative discourse toward a value-based and technology-enabled managerial framework. Theoretical contributions include the conceptualization of a maqashid shariah-oriented digital management framework and an ecosystem perspective on halal industry development. These insights offer practical implications for policymakers, practitioners, and academics, while also highlighting the need for future empirical and cross-country research to strengthen theory and practice in Islamic business management.